Methodological analysis of boxing activity profile by category - Puchol Devesa, V.; Caparros Pons, T. (Journal of Physical Education and Sport, 2020)
Introduction: The purpose of this research is to carry out an observational descriptive analysis to create an analysis instrument that determines the most relevant patterns and characteristics of boxing, so that useful bases can be established to create links in the planning process based on winning strategies. Material and Methods: The sample includes eight elite male boxers from the Welter category of the London 2012 Olympics, with an age range of 21 to 28 years (mean = 24.50 ± 2.20) and weight 64-69 kg (defined by their category). Results: A descriptive analysis is undertaken of the average points per match, the main technical/tactical actionsand the time percentage of the motor actions involved during the round. Based on the normality of the sample, the difference between the variables is determined with the Kruskall-Wallis Test. The statistical correlation technique is used to evaluate possible relationships between the variables to the average points per match with the Spearman Rho test. Five significant correlations stand out, two positive and three negative, including: Blows landed (rho = 0.740), % Blows landed (rho = 0.581), Blocks (rho = -0.635), %T. Block (rho = -0.661) and Blows evaded (rho = -0.540) and average points per match. Finally, a multiple linear regression is made between the average points, the technical/tactical actions and the time percentage of the motor actions (R2 = 0.76). Discussion: winner launches more blows during the round and creates more time for attack actions, which would justify the reason for his lower records minors in terms of Blows evaded, Blocks, % Blocks, %T. Blocking and %T. Null. His average Blows landed and % Blows landed are also higher, he launches more blows and so have more chances of hitting the valid scoring zone, because he maintains a higher frequency of attack manoeuvres and because his accuracy in striking is more efficient. Conclusion: The results establish that in this particular category and that, to win an event of this nature, the boxers have to move around the ring through the work of the lower body more than half of the round, maintain a high offensive and defensive action activity and optimum precision in the blows executed.